Cylindrical porous radiant burner with internal combustion regime: Energy saving analysis using response surface method. (15th September 2020) - Vahidhosseini, Seyed Mohammad; Esfahani, Javad Abolfazli; Kim, Kyung Chun
Abstract: A response surface analysis is performed on a cylindrical porous radiant burner with internal combustion regime, which is recently introduced. A structured grid is used to perform the simulations. First, the equations of continuity, momentum, turbulence, energy, radiation, mixture fraction and progress variable were solved with an appropriate accuracy. An excellent agreement was observed between the numerical results and the available laboratory data. Second, three response surfaces of the output enthalpy, radiant efficiency and radiative heat were investigated using the verified model. The independent variables including input power, porous foam's emissivity and the equivalence ratio are changed in the ranges of P  ∈ [1.5, 5] kW, ε rad ∈ [0.4, 0.9] and φ  ∈ [0.5, 1.1], respectively. The results show that the radiant efficiency of above 50% can be achieved using this type of porous burner with no preheating. Based on a local sensitivity analysis, the sensitivity of η rad to ε rad and φ at ( P, ε rad, φ ) = (5, 0.4, 0.8) is equal to 7.50% and 0.511%, according to the coded independent variables, respectively. Moreover, according to an energy saving analysis, for a radiant heat of 900 W, 13.6% of energy could be saved compared to the ideal conditions, in which φ ≈ 1, by choosing the best conditions. Highlights: A recently introduced porous radiant burner is modeled numerically. A radiant efficiency of above 50% is achieved without any preheating. Energy and fuel saving analysis is performed using the RSM. Power, emissivity and equivalence ratio are selected as the independent variables. The best and worst conditions are introduced from energy saving point of view.